2022
DOI: 10.1002/adem.202200126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trace Boron Addition and Different Arc Types on Microstructure and Mechanical Properties of TC11/TC17 Dual Alloy Fabricated by Wire Arc Additive Manufacturing

Abstract: Wire arc additive manufacturing (WAAM) provides an efficient and low‐cost potential for manufacturing TC11/TC17 dual titanium alloy. In this work, six deposition samples were fabricated for the test of microstructure and mechanical properties by the combination of trace boron addition and different arc types (direct current (DC), high frequency pulsed current (HC), low frequency pulsed current (LC)). Results show that the epitaxial growth β columnar grains were formed except for the combination of low frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…However, the coarse microstructure and significant anisotropy was easily obtained in the titanium alloy arc plasma-based additive manufacturing part. Some researchers proposed additional nucleation particles to improve the titanium alloy part [ 9 , 10 , 11 ]. Zhuo et al [ 11 ] researched the influence of trace boron addition on microstructure and mechanical properties of TC11/TC17 in wire arc additive manufacturing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the coarse microstructure and significant anisotropy was easily obtained in the titanium alloy arc plasma-based additive manufacturing part. Some researchers proposed additional nucleation particles to improve the titanium alloy part [ 9 , 10 , 11 ]. Zhuo et al [ 11 ] researched the influence of trace boron addition on microstructure and mechanical properties of TC11/TC17 in wire arc additive manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers proposed additional nucleation particles to improve the titanium alloy part [ 9 , 10 , 11 ]. Zhuo et al [ 11 ] researched the influence of trace boron addition on microstructure and mechanical properties of TC11/TC17 in wire arc additive manufacturing. The results showed that the coarser α phases surrounding thin α phases were formed, and β grain size was refined obviously.…”
Section: Introductionmentioning
confidence: 99%